Nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide and preparation method of nickel-manganese diatomic catalyst
By preparing nickel-manganese diatomic catalysts, the problems of few active sites and weak adsorption capacity of existing CO2 electrocatalysts are solved, and the CO2 electroreduction effect with high selectivity and high reaction current density is achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202411543881.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
The existing CO2 electrocatalysts have problems such as few active sites, poor catalytic performance, small specific surface area, and weak adsorption ability to CO2, resulting in low selectivity of CO2 electroreduction products and easy blockage and failure of catalysts.
Using the preparation method of nickel-manganese diatomic catalyst, mixing 2-methylimidazole, zinc nitrate, nickel nitrate and manganese nitrate in methanol to form a mixed solution to form a ZIF-8 precursor, and pyrolysis and pickling through high temperature. Steps to form a nickel-manganese diatom catalyst, providing rich active sites and porous structures, and improving catalytic performance.
It improves the selectivity of CO2RR and reaction current density, improves the catalytic activity of the catalyst and the Faraday efficiency of the product CO, extends the service life of the catalyst, and is suitable for large-scale production.
Smart Images

Figure CN119243223A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide and a preparation method thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] CO2 capture, utilization and storage technology can reduce the concentration of CO2 in the atmosphere and reduce greenhouse gas emissions. CO2 utilization technology uses new energy as a driving force to convert CO2 into C1 chemical fuels and multi-carbon chemicals. This technology can achieve stable storage of new energy and resource utilization of CO2 gas, get rid of dependence on fossil energy, change the energy structure from the source, and improve the utilization efficiency of new energy.
[0004] In the process of electrocatalytic CO2 reduction reaction to produce fuel, the electrocatalyst can specifically reduce the activation energy of a product reaction and regulate the adsorption and dissociation of CO2, so that different electrocatalysts used in the reaction will result in different types and selectivities of products. In recent years, transition metals such as Ni, Fe, and Mn have been widely used to prepare CO2 electroreduction catalysts, but current catalysts generally have few active sites and poor catalytic performance; small specific surface area, weak adsorption capacity for CO2, and thus adversely affect catalytic activity; CO2 electroreduction catalytic product CO has low selectivity, and catalytic reduction products such as C will also be produced, and the produced carbon is easy to deposit on the surface of the catalyst, causing problems such as catalyst blockage and failure. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide and a preparation method thereof, which has high product selectivity and high reaction current density.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide, comprising the following steps:
[0008] Dissolve 2-methylimidazole, zinc nitrate, nickel nitrate and manganese nitrate in methanol in proportion to prepare a mixed solution, and stir at 20-35° C. for 20-30 hours;
[0009] After the stirring is completed, the solid and liquid are separated, the solid is washed, dried, and ground, and then the ground powder is pyrolyzed in an inert atmosphere to obtain a catalyst;
[0010] The catalyst is heated and acid-washed, alcohol-washed and water-washed with a sulfuric acid solution, and then dried to obtain a nickel-manganese diatomic catalyst.
[0011] 2-Methylimidazole, zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate are dissolved in methanol in proportion. Methanol has strong solubility and a mixed solution can be prepared. The solution is stirred at 20-35°C for 20-30h (a Ni / Mn-doped ZIF-8 precursor is generated in the mixed solution. The zinc source is evaporated by high-temperature pyrolysis of ZIF-8, and then Ni atoms and Mn atoms replace Zn atoms and are anchored in the nitrogen-carbon skeleton to generate reaction activation sites). 2-Methylimidazole and zinc nitrate generate ZIF-8, while hydrated nickel nitrate and hydrated manganese nitrate provide nickel and manganese sources. A Ni / Mn-doped ZIF-8 precursor is generated in the mixed solution. The zinc source is evaporated by high-temperature pyrolysis of ZIF-8, and then Ni atoms and Mn atoms replace Zn atoms and are anchored in the nitrogen-carbon skeleton to generate reaction activation sites.
[0012] After the stirring is completed, the solid and liquid are separated, the solid is washed, dried, and ground, and then the ground powder is pyrolyzed in an inert atmosphere (such as N2, etc., the inert gas can provide a protective atmosphere to prevent the product from being oxidized) to obtain a catalyst;
[0013] The catalyst is heated and pickled with a strong acid solution (sulfuric acid, hydrochloric acid, etc.) (pickling can remove carbonized impurities or residual metal atom clusters and enhance reaction activity), washed with alcohol and washed with water, and then dried to obtain a nickel-manganese diatomic catalyst. Pickling can remove carbonized impurities or residual metal atom clusters and enhance reaction activity.
[0014] Zinc ZIF is doped with nickel-manganese transition metal. Thanks to the crystal structure of ZIF-8, the zinc source can be evaporated after carbonization to obtain a nitrogen-carbon skeleton and atomic vacancies, and the nickel-manganese element can replace the zinc source to anchor on the nitrogen-carbon skeleton in a single-atom state and distribute evenly at the atomic level (thanks to the crystal structure of ZIF-8, the zinc source can be evaporated after carbonization to obtain a nitrogen-carbon skeleton and atomic vacancies, and the nickel-manganese element can replace the zinc source to anchor on the nitrogen-carbon skeleton in a single-atom state and distribute evenly at the atomic level), forming a nickel-manganese diatomic electrochemical reaction activation site, and the catalyst has a porous structure, with high selectivity and high current density for electrocatalytic reduction to prepare CO.
[0015] Heating and pickling the catalyst with a sulfuric acid solution can remove clustered metal atoms and other excess impurities, improve the purity of the diatomic catalyst, and thus help improve the catalytic performance of the nickel-manganese diatomic catalyst.
[0016] In some embodiments, the ratio of the total molar amount of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate to the molar amount of 2-methylimidazole is 1:5-7, preferably 1:6.
[0017] Preferably, the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate is 0.8-1.2:1.5-2.5:0.01-0.3.
[0018] More preferably, the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate is 0.8-1.2:1.5-2.5:0.1-0.3.
[0019] More preferably, the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate is 1:2:0.18-0.22, preferably 1:2:0.2.
[0020] In some embodiments, after stirring, the solid and liquid are separated, and the solid is washed with methanol for 2-4 times. Methanol has a strong dissolving ability and can wash away the nitrate residue in the ZIF precursor obtained by centrifugation.
[0021] In some embodiments, the method of drying the solid after washing is: drying overnight in a vacuum environment, where the vacuum environment can prevent the precursor from being oxidized by air during drying.
[0022] Preferably, the drying temperature under vacuum environment is 55-65°C.
[0023] In some embodiments, the pyrolysis temperature is 900-1100° C., and the pyrolysis time is 3-5 h.
[0024] Preferably, the heating rate during the pyrolysis process is 2-5°C min -1 , preferably 3℃min -1 .
[0025] In some embodiments, the stirring is magnetic stirring, the rate of the magnetic stirring is 600-1000 rpm, and the stirring time is 22-25 h.
[0026] In some embodiments, a mixed solution of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate and a 2-methylimidazole solution are prepared respectively, and then the two solutions are mixed, and the metal nitrate solution is slowly added to the 2-methylimidazole solution to ensure sufficient reaction and generate a ZIF-8 precursor.
[0027] In some embodiments, the concentration of the sulfuric acid solution is 1-2M.
[0028] Preferably, the pickling is oil bath pickling, the temperature of the oil bath is 70-90°C, and the pickling time is 8-12h. At this temperature, water evaporates quickly in the water bath. If cold water is continuously added, the temperature of the water bath heating will be affected, which will have a certain adverse effect on the reaction. Therefore, an oil bath is selected to stabilize the reaction environment.
[0029] In some embodiments, the alcohol washing is washing with methanol, and the number of methanol washings is 2-4 times; the number of water washings is 2-4 times.
[0030] Preferably, the solid washed with acid, alcohol and water is dried overnight in a vacuum environment at 55-65° C. to obtain the nickel-manganese diatomic catalyst.
[0031] In a second aspect, the present invention provides a nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide, which is prepared by the preparation method.
[0032] In a third aspect, the present invention provides the use of the nickel-manganese diatomic catalyst in catalyzing the electrochemical reduction of carbon dioxide to produce carbon monoxide.
[0033] In some embodiments, when catalyzing the electrochemical reduction of carbon dioxide to produce carbon monoxide, the applied voltage is -0.2 to -1.2 V vs. RHE.
[0034] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0035] The nickel-manganese diatomic catalyst prepared by the preparation method of the present invention has excellent CO2RR (Electrocatalytic CO2 Reduction Reaction) performance (i.e., electrocatalytic carbon dioxide reduction reaction performance), improves the selectivity of CO in the electroreduction product, and has excellent CO Faraday efficiency (FE) and reaction current density.
[0036] The inventors believe that the catalyst prepared by the present invention has excellent electrocatalytic performance mainly due to the fact that the two metal elements are dispersed at the atomic level in the carbon-nitrogen skeleton, providing abundant active sites, which is conducive to the transfer of electrons and improves the catalytic activity of the catalyst. That is to say, compared with a single transition metal single-atom catalyst, taking a nickel single-atom catalyst as an example, the presence of nickel-manganese diatoms provides more activation sites. The catalyst provided by the present invention has a high specific surface area, and the pore-forming effect during the pyrolysis process can promote the formation of a rich porous structure on the carbon-nitrogen carrier, greatly promoting the CO2 adsorption capacity and improving the catalytic activity. In addition, the strong charge transfer of the diatomic coordination environment allows the diatomic electronic structure to be effectively optimized.
[0037] In the preparation method of the catalyst of the present invention, the crystal structure and performance of the catalyst can be adjusted by controlling the ratio of the metal nitrate hydrate, thereby preparing catalysts with different specific structures and performances. Selecting a suitable carrier can further increase the metal single atom loading, thereby further improving the catalytic performance. Therefore, the atomic metal catalyst prepared by the present invention can promote CO2RR-related activities, thereby improving the catalytic activity of the catalyst.
[0038] In addition, the preparation method of the present invention is simple to operate and only requires one pyrolysis, thus avoiding energy waste caused by multiple pyrolysis, and can further improve the catalyst output ratio. It is very suitable for large-scale production and has important value. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0040] Figure 1 is a scanning electron microscope (SEM) image of the nickel-manganese diatomic catalyst synthesized in Example 1 of the present invention;
[0041] Figure 2 The linear sweep voltammetry curve (LSV) of the nickel-manganese diatomic catalyst synthesized in Example 1 of the present invention for electrocatalyzing CO2 to produce CO in a flow-type electrolytic cell;
[0042] Figure 3 The linear sweep voltammetry curve (LSV) of the nickel-manganese diatomic catalyst synthesized in Comparative Example 1 of the present invention for electrocatalyzing CO2 to produce CO in a flow-type electrolytic cell;
[0043] Figure 4 The linear sweep voltammetry curve (LSV) of the nickel-manganese diatomic catalyst synthesized in Example 2 of the present invention for electrocatalyzing CO2 to produce CO in a flow-type electrolytic cell;
[0044] Figure 5 The linear sweep voltammetry curve (LSV) of the nickel-manganese diatomic catalyst synthesized in Example 3 of the present invention for electrocatalyzing CO2 to produce CO in a flow-type electrolytic cell;
[0045] Figure 6 This is a Faraday efficiency diagram of the nickel-manganese diatomic catalyst synthesized in Example 1 of the present invention for electrocatalyzing CO2 to produce CO in a flow-type electrolytic cell;
[0046] Figure 7 is the electrochemical impedance spectroscopy (EIS) curve of CO2RR of the nickel-manganese diatomic catalyst synthesized in Example 1 of the present invention in a flow-type electrolytic cell;
[0047] in, Figures 2 to 7 Among them, Ni x Mn y The catalyst named Ni-NC represents that the molar ratio of nickel metal nitrate hydrate to manganese metal nitrate hydrate is x:y, and the catalyst named Ni-NC represents that there is no manganese metal nitrate hydrate doping, and the prepared catalyst is a nickel single atom catalyst. DETAILED DESCRIPTION
[0048] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0049] The present invention will be further described below in conjunction with the embodiments.
[0050] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art, and the operations are performed at room temperature.
[0051] Example 1
[0052] Ni1Mn 0.2 Preparation of -NC diatomic catalysts:
[0053] First, according to the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate of Zn(NO3)2·6H2O:Ni(NO3)2·6H2O:Mn(NO3)2·4H2O=1:2:0.4, 5mmol 1.487g Zn(NO3)2·6H2O, 10mmol 2.908g Ni(NO3)2·6H2O and 2mmol 0.502g Mn(NO3)2·4H2O were weighed into a beaker, 200ml methanol was poured into it, and ultrasonic dispersion was performed for 15 minutes to form solution A;
[0054] According to the ratio of the total molar amount of zinc nitrate, nickel nitrate and manganese nitrate to the molar amount of 2-methylimidazole being 1:6, 8.364 g of 2-methylimidazole was weighed into a beaker, 100 ml of methanol was poured into it, and ultrasonic dispersion was performed for 15 minutes to form a solution B.
[0055] At a speed of 700 rpm, solution A was slowly poured into solution B to form a mixed solution. The magnetic stirrer maintained a speed of 700 rpm. The mixed solution was stirred at room temperature for 24 hours to prepare Ni 2+ With Mn 2+ Doped ZIF-8 precursor.
[0056] After the magnetic stirring was completed, the mixed solution was centrifuged, and the solid was washed four times with methanol. The sediment was collected and dried overnight at 60° C. under vacuum.
[0057] After vacuum drying, the sample was naturally cooled to room temperature, and then the dried sample was taken out and ground in an agate grinding mortar for 15 minutes into powder. The powder was then placed in a quartz boat and then placed in a tube furnace to complete pyrolysis under the protection of N2 atmosphere. The N2 flow rate was 100 ml min -1 The pyrolysis temperature was 1000 °C and the heating rate was 3 °C min -1, keep a constant temperature at 1000°C for 4 hours, then cool naturally to obtain catalyst carbonized powder.
[0058] 100 mL of 1 M sulfuric acid solution was added to the carbonized catalyst powder, and the powder was acid-washed by stirring in an oil bath pot. The oil bath environment was maintained at 80° C. and the acid-washing was carried out by stirring for 8 hours.
[0059] After acid washing, centrifugation was performed, and the mixture was washed with methanol and deionized water respectively, and dried under vacuum at 60°C overnight to obtain Ni1Mn 0.2 -NC diatomic catalyst, its SEM image is as follows Figure 1 As shown, the prepared catalyst has a rich porous structure.
[0060] Comparative Example 1
[0061] Preparation of Ni-NC single atom catalyst:
[0062] First, 5 mmol 1.487 g Zn(NO3)2·6H2O and 10 mmol 2.908 g Ni(NO3)2·6H2O were weighed into a beaker according to the molar ratio of zinc nitrate hexahydrate to nickel nitrate hexahydrate of Zn(NO3)2·6H2O:Ni(NO3)2·6H2O=1:2, and 200 ml of methanol was poured into the beaker, and ultrasonic dispersion was performed for 15 minutes to form a solution A;
[0063] According to the ratio of the total molar amount of zinc nitrate and nickel nitrate to the molar amount of 2-methylimidazole being 1:6, 7.38 g of 2-methylimidazole was weighed into a beaker, 100 ml of methanol was poured into it, and solution B was formed by ultrasonic dispersion for 15 minutes.
[0064] At a speed of 700 rpm, solution A was slowly poured into solution B to form a mixed solution. The magnetic stirrer was kept at a speed of 700 rpm. The mixed solution was stirred at room temperature for 24 hours to prepare Ni 2+ With Mn 2+ Doped ZIF-8 precursor.
[0065] After the magnetic stirring was completed, the mixed solution was centrifuged and washed with methanol three times, and the sediment was collected and dried at 60°C in a vacuum environment overnight.
[0066] After vacuum drying, the sample was taken out and ground into powder in an agate mortar for 15 minutes. The powder was then placed in a quartz boat and then placed in a tube furnace to complete pyrolysis under N2 atmosphere protection. The N2 flow rate was 100 ml min -1 The pyrolysis temperature was 1000 °C and the heating rate was 3 °C min -1 , keep a constant temperature at 1000°C for 4 hours, then cool naturally to obtain catalyst carbonized powder.
[0067] Add 100 mL of 1M sulfuric acid solution to the carbonized catalyst powder, stir and pickle in an oil bath pot, maintain an oil bath environment of 80°C, and stir and pickle for 8 hours. After pickling, centrifuge and wash with methanol and deionized water respectively, and vacuum dry at 60°C overnight to finally obtain a Ni-NC catalyst.
[0068] Example 2
[0069] Ni1Mn 0.1 Preparation of -NC diatomic catalysts:
[0070] First, according to the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate of Zn(NO3)2·6H2O:Ni(NO3)2·6H2O:Mn(NO3)2·4H2O=1:2:0.2, 5mmol 1.487g Zn(NO3)2·6H2O, 10mmol 2.908g Ni(NO3)2·6H2O and 1mmol 0.251g Mn(NO3)2·4H2O were weighed into a beaker, 200ml methanol was poured into it, and ultrasonic dispersion was performed for 15 minutes to form solution A;
[0071] According to the ratio of the total molar amount of zinc nitrate, nickel nitrate and manganese nitrate to the molar amount of 2-methylimidazole being 1:6, 7.872 g of 2-methylimidazole was weighed into a beaker, 100 ml of methanol was poured into it, and ultrasonic dispersion was performed for 15 minutes to form a solution B.
[0072] At a speed of 700 rpm, solution A was slowly poured into solution B to form a mixed solution. The magnetic stirrer was kept at a speed of 700 rpm. The mixed solution was stirred at room temperature for 24 hours to prepare Ni 2+ With Mn 2+ Doped ZIF-8 precursor.
[0073] After the magnetic stirring was completed, the mixed solution was centrifuged and washed with methanol three times, and the sediment was collected and dried at 60°C in a vacuum environment overnight.
[0074] After vacuum drying, the sample was naturally cooled to room temperature, and then the dried sample was taken out and ground in an agate grinding mortar for 15 minutes into powder. The powder was then placed in a quartz boat and then placed in a tube furnace to complete pyrolysis under the protection of N2 atmosphere. The N2 flow rate was 100 ml min -1 The pyrolysis temperature was 1000 °C and the heating rate was 3 °C min -1 , keep a constant temperature at 1000°C for 4 hours, then cool naturally to obtain catalyst carbonized powder.
[0075] Add 100 ml of 1M sulfuric acid solution to the carbonized catalyst powder, stir and pickle in an oil bath pot, maintain an 80°C oil bath environment, and stir and pickle for 8 hours. After pickling, centrifuge and wash with methanol and deionized water respectively, and dry in vacuum at 60°C overnight to finally obtain Ni1Mn 0.1 -NC diatomic catalyst.
[0076] Example 3
[0077] Ni1Mn 0.3 Preparation of -NC diatomic catalysts:
[0078] First, 5 mmol 1.487 g Zn(NO3)2·6H2O, 10 mmol 2.908 g Ni(NO3)2·6H2O and 3 mmol 0.753 g Mn(NO3)2·4H2O were weighed into a beaker according to the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate of Zn(NO3)2·6H2O:Ni(NO3)2·6H2O:Mn(NO3)2·4H2O=1:2:0.6, and 200 ml of methanol was poured into the beaker, followed by ultrasonic dispersion for 15 minutes to form a solution A;
[0079] According to the ratio of the total molar amount of zinc nitrate, nickel nitrate and manganese nitrate to the molar amount of 2-methylimidazole being 1:6, 8.856 g of 2-methylimidazole was weighed into a beaker, 100 ml of methanol was poured into it, and ultrasonic dispersion was performed for 15 minutes to form a solution B.
[0080] At a speed of 700 rpm, solution A was slowly poured into solution B to form a mixed solution. The magnetic stirrer maintained a speed of 700 rpm. The mixed solution was stirred at room temperature for 24 hours to prepare Ni 2+ With Mn 2+ Doped ZIF-8 precursor.
[0081] After the magnetic stirring, the mixed solution was centrifuged and washed with methanol three times, and the sediment was collected and dried at 60°C in a vacuum environment overnight.
[0082] After vacuum drying, the sample was naturally cooled to room temperature, and then the dried sample was taken out and ground into powder in an agate grinding mortar for 15 minutes. The powder was then placed in a quartz boat and then placed in a tube furnace to complete pyrolysis under the protection of N2 atmosphere. The N2 flow rate was 100 ml min -1 The pyrolysis temperature was 1000 °C and the heating rate was 3 °C min -1 , keep a constant temperature at 1000°C for 4 hours, then cool naturally to obtain catalyst carbonized powder.
[0083] Add 100 ml of 1M sulfuric acid solution to the carbonized catalyst powder, stir and pickle in an oil bath pot, maintain an 80°C oil bath environment, and stir and pickle for 8 hours. After pickling, centrifuge and wash with methanol and deionized water respectively, and dry in vacuum at 60°C overnight to finally obtain Ni1Mn 0.3 -NC diatomic catalyst.
[0084] Example 4
[0085] Application of nickel-manganese diatomic catalysts in the electrocatalytic reduction of CO2 to produce CO:
[0086] A three-electrode measurement was performed using a custom-made flow-type electrolytic cell consisting of a cathode, an anode, and an ion exchange membrane. 0.1 -NC, Ni1Mn 0.2 -NC, Ni1Mn 0.3 -NC or Ni-NC catalyst was mixed with 500 μL isopropanol and 4 μL 5% Nafion117 solution. The mixed catalyst slurry was then ultrasonically dispersed for 30 minutes, and then the catalyst slurry was coated on a 1.5×1.5 cm carbon paper with a microporous carbon layer as the working electrode cathode, with a catalyst loading of about 1.0 mg cm -2 .
[0087] A platinum sheet was used as the anode, a Nafion 117 ion exchange membrane was sandwiched between the cathode and cathode, and an Ag / AgCl electrode of a saturated KCl solution was used as the reference electrode.
[0088] A 1.0 M KOH solution was used as the cathode and anode electrolyte, and a peristaltic pump was used to control the electrolyte flow at a rate of approximately 30 mL min -1 The speed circulates continuously between the cathode and anode.
[0089] During the entire test process, the flow rate of CO2 entering the cathode side is 50 sccm. The voltage applied to the cathode during the CO2 electrochemical reduction reaction is -0.2 to -1.2 V vs. RHE. It should be specially noted that the LSV data obtained by the test of the present invention are not IR corrected.
[0090] See also Figure 1 It can be seen that the nickel-manganese diatomic catalyst Ni1Mn prepared in Example 1 0.2 -NC has rich porous structure.
[0091] See also Figure 2 , the nickel-manganese diatomic catalyst Ni1Mn prepared in Example 1 0.2 -NC in the flow-type electrolytic cell, the cathode voltage applied was -1.2 V vs. RHE, and the cathode reduction reaction current density was 414 mA cm -2, far exceeding the industrial current density (>200mA cm -2 ) requirements.
[0092] See also Figure 3 In the flow-type electrolytic cell, the cathode voltage applied to the nickel single-atom catalyst Ni-NC prepared in Comparative Example 1 was -1.2 V vs. RHE, and the cathode reduction reaction current density was 220 mA cm -2 Thanks to the introduction of manganese metal, Ni1Mn 0.2 -NC catalyst has more reactive activation sites, Ni1Mn 0.2 Compared with Ni-NC, the reaction current density of -NC is increased by about one-fold at a voltage of -1.2Vvs.RHE, and the performance is significantly improved.
[0093] See also Figure 4 , the nickel-manganese diatomic catalyst Ni1Mn prepared in Example 2 0.1 -NC in the flow-type electrolytic cell, the cathode voltage applied was -1.2 V vs. RHE, and the cathode reduction reaction current density was 270 mA cm -2 ,Ni1Mn 0.1 -NC compared to Ni1Mn 0.2 -NC has a reaction current density of 34.78% lower when the voltage is -1.2V vs. RHE, but it is increased by 22.72% compared with Ni-NC.
[0094] See also Figure 5 , the nickel-manganese diatomic catalyst Ni1Mn of Example 3 0.3 -NC in the flow-type electrolytic cell, the cathode voltage applied was -1.2 V vs. RHE, and the cathode reduction reaction current density was 250 mA cm -2 ,Ni1Mn 0.3 -NC increases the reaction current density by 13.63% compared with Ni-NC.
[0095] It can be seen that Ni x Mn y -NC diatomic catalysts with excessive or insufficient Mn doping ratios will lead to a decrease in the performance of the diatomic catalyst, which is attributed to the excessive introduction of manganese metals, which will reduce the exposure of nickel atoms and reduce the reaction activity, while the insufficient introduction of manganese metals is not conducive to the formation of nickel-manganese diatomic activation sites, reducing the intrinsic activity of the diatomic catalyst. Both of these will lead to a decrease in the reaction current density.
[0096] See also Figure 6 It can be seen that the nickel-manganese diatomic catalyst Ni1Mn prepared in Example 1 0.2In a flow electrolytic cell, the Faradaic efficiency of CO products of -NC is above 95% at a wide potential range of -0.2 to -1.2 V vs. RHE, which shows excellent product selectivity and great potential for commercial applications.
[0097] See also Figure 7 , the nickel-manganese diatomic catalyst Ni1Mn prepared in Example 11 0.2 In the electrochemical impedance spectroscopy (EIS) curve of CO2RR in a flow-type electrolytic cell, the solution resistance of -NC was 4.8Ω, while that of Ni1Mn 0.2 -NC charge transfer resistance is only 1.05Ω. Smaller charge transfer resistance can accelerate electron transfer in the catalyst and help improve current density.
[0098] Compared with the prior art, the present invention improves the synthesis method of the catalyst, the method is simple, and the yield is improved. The method can effectively increase the specific surface area of the catalyst, provide abundant active sites, thereby facilitating the transfer of electrons and improving the catalytic activity of the nickel-manganese diatomic catalyst. The synthesis method is simple to operate, the conditions are convenient, it is suitable for large-scale production, has significant green benefits and economic benefits, and can be widely used in the field of carbon dioxide electrocatalytic reduction.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide, characterized in that: The steps include: Dissolve 2-methylimidazole, zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate in methanol in proportion to prepare a mixed solution, and stir at 20-35° C. for 20-30 hours; After the stirring is completed, the solid and liquid are separated, the solid is washed, dried, and ground, and then the ground powder is pyrolyzed in an inert atmosphere to obtain a catalyst; The catalyst is heated and acid-washed, alcohol-washed and water-washed with a strong acid solution and then dried to obtain a nickel-manganese diatomic catalyst.
2. The method for preparing the nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The ratio of the total molar amount of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate to the molar amount of 2-methylimidazole is 1:5-7, preferably 1:6; Preferably, the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate is 0.8-1.2:1.5-2.5:0.01-0.3; Preferably, the molar ratio of zinc nitrate hexahydrate, nickel nitrate hexahydrate and manganese nitrate tetrahydrate is 0.8-1.2:1.5-2.5:0.1-0.3; Preferably, the molar ratio of zinc nitrate, nickel nitrate and manganese nitrate is 1:2:0.18-0.22, preferably 1:2:0.
2.
3. The method for preparing the nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: After the stirring is completed, the solid and liquid are separated, and the solid is washed with methanol for 2-4 times.
4. The method for preparing the nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The method of washing and drying the solid is: drying overnight under a vacuum environment; Preferably, the drying temperature under vacuum environment is 55-65°C.
5. The method for preparing the nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The pyrolysis temperature is 900-1100°C, and the pyrolysis time is 3-5h; Preferably, the heating rate during the pyrolysis process is 2-5°C min -1 , preferably 3℃min -1 ; Preferably, the stirring is magnetic stirring, the rate of the magnetic stirring is 600-1000 rpm, and the stirring time is 22-25 h.
6. The method for preparing the nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: Firstly, a mixed solution of zinc nitrate, nickel nitrate and manganese nitrate and a 2-methylimidazole solution are prepared separately, and then the two solutions are mixed.
7. The method for preparing the nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The concentration of the sulfuric acid solution is 1-2M; Preferably, the pickling is oil bath pickling, the temperature of the oil bath is 70-90° C., and the pickling time is 8-12 h.
8. The method for preparing the nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide according to claim 1, characterized in that: The alcohol washing is performed by methanol washing, and the number of methanol washings is 2-4 times; the number of water washings is 2-4 times; Preferably, the solid washed with acid, alcohol and water is dried overnight in a vacuum environment at 55-65° C. to obtain the nickel-manganese diatomic catalyst.
9. A nickel-manganese diatomic catalyst for electrochemical reduction of carbon dioxide, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the nickel-manganese diatomic catalyst according to claim 9 in catalyzing the electrochemical reduction of carbon dioxide to produce carbon monoxide; Preferably, when catalyzing the electrochemical reduction of carbon dioxide to produce carbon monoxide, the applied voltage is -0.2 to -1.2 V vs. RHE.
Citation Information
Cited By
Nickel monatomic electrocatalyst with surface cavity structure as well as preparation method and application of nickel monatomic electrocatalyst
CN120174406A
Nickel monatomic electrocatalyst with surface cavity structure and preparation method and application thereof
CN120174406B
